2009
DOI: 10.1108/02640470910979589
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous library usability test for the improvement of information access for the blind

Abstract: PurposeUsability tests to improve information accessibility for the blind have rarely been carried out. Recently, the LG Digital Talking Book (LG DTB) Library has developed a ubiquitous service, which provides the blind with library service anytime, anywhere, using mobile phones with the automated library access procedure. The main purpose of this paper is to draw up a better plan to improve information accessibility for the blind through the usability test of the service being made by the LG DTB Library.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…As memory gets smaller over time, such devices will continue to get smaller or better still, subsumed as software into existing cellular phones. In fact, research examining the preferences of visually-impaired users has found a that cellular phones as audio book listening methods were preferred to not only devices such as Voiceye and DAISY readers, but also the internet [25]. Nonetheless, the experience of Voiceye in South Korea is indicative of how a combination of how new technology and a policy initiative to create more accessible material for people with disabilities.…”
Section: Mobile Accessibilitymentioning
confidence: 95%
“…As memory gets smaller over time, such devices will continue to get smaller or better still, subsumed as software into existing cellular phones. In fact, research examining the preferences of visually-impaired users has found a that cellular phones as audio book listening methods were preferred to not only devices such as Voiceye and DAISY readers, but also the internet [25]. Nonetheless, the experience of Voiceye in South Korea is indicative of how a combination of how new technology and a policy initiative to create more accessible material for people with disabilities.…”
Section: Mobile Accessibilitymentioning
confidence: 95%
“…Since these projects focussed on different issues, and use a different mixture of these components, we restrict ourselves to a brief overview of the differences and similarities. As with Access Sight, a primary use of text-to-speech technology in DL systems has been to provide capabilities for print-disabled users such as the visually impaired [2,24,25]. While the "hands-free" aspect is of relevance to this work, our requirements are not so strict.…”
Section: Digital Library Systemsmentioning
confidence: 99%
“…Mobile and wireless communication technologies have tremendous effects on libraries, which integrate existing information and new technologies to provide a reader-centred environment and more convenient services (Joo and Yeon Lee, 2011;Pant, 2015;Tu and Hwang, 2018). However, for the socially disadvantaged (such as the disabled), more specific needs are often neglected, hindering their rights to access digital information services (Kwak and Bae, 2009;Majinge and Mutula, 2018). The trend in international requirements specifically indicates that libraries are committed to providing equal access to collections, services and facilities for all library users, including patrons with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the LG Digital Talking Book Library developed a ubiquitous service for the visually impaired and provided voice book services for them to visit libraries anytime and anywhere via the internet on cellphones. Kwak and Bae (2009) indicated that for the visually impaired, the status of publication updates, asymmetrical subject areas and lack of educational content were the more serious problems, while handy-to-carry information terminals, such as cellphones, were favoured. Yoon et al (2016) and Xie et al (2020) further pointed out that usability is important for digital libraries to support blind and visually impaired users in actively searching for information instead of passively waiting for them to seek help.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation